Immunization practices in acute lymphocytic leukemia and post-hematopoietic stem cell transplant in Canadian Pediatric Hematology/Oncology centers. Issue 4 (2nd April 2016) - Top, Karina A.; Pham-Huy, Anne; Price, Victoria; Sung, Lillian; Tran, Dat; Vaudry, Wendy; Halperin, Scott A.; De Serres, Gaston
ABSTRACT: There are no Canadian immunization guidelines for children treated for malignancy. Guidelines do exist for patients who underwent hematopoietic stem cell transplant (HSCT), but they provide broad timeframes for initiating vaccination; there is no standard schedule. The optimal approach to immunization in these populations is unclear. We sought to describe immunization practices at Canadian Pediatric Hematology/Oncology centers. A 43-item online questionnaire was distributed to the 16 programs in the C 17 research network of pediatric hematology/oncology centers to capture information on timing and criteria for immunization of patients with acute lymphocytic leukemia (ALL) and those who have undergone HSCT. At each center, 1–2 physicians or pharmacists completed the survey to reflect center-wide immunization practices. Responses were received from 11/16 (69%) programs; 11 respondents reported on practices for patients with ALL and 9 reported on practices for patients who are post-HSCT. In 5/11 ALL programs (45%) re-immunization is recommended routinely after chemotherapy, starting 3–6 months post-chemotherapy. In HSCT programs, timing of pneumococcal conjugate vaccination (PCV) varied from 3 months post-HSCT (4 programs) to 12 months post-HSCT (4 programs). Live vaccines were administered 24 months post-HSCT in 8/9 programs. All HSCT programs considered graft-versus-host-disease and 7 considered discontinuation of immunosuppression in immunization decisions. Pediatric hematology/oncology programs were divided in regards to re-immunization of patients with ALL post-chemotherapy. After HSCT, timing of PCV administration varied, with 4 programs initiating immunization later than Canadian guidelines recommend (3–9 months post-HSCT). These findings suggest a need to standardize immunization practices in these populations.